Culture and Identity in Selected New Media Artworks in Malaysia 1993-2007 - Sarena Abdullah; Siti Khadijah Elham (Journal of Visual Art and Design, 2019)
Contextual analysis studies based on cultural and identity aspects of fine art practice are still limited in Malaysia, especially concerning new media art, although new media as an artistic tool was introduced as early as the 1990s. Since the seminal exhibition on E-art was in 1997, since then systematic examination of new media artworks and their role in the Malaysian art history has only been limitedly done. The early approaches of new media art were varied, yet the subject matter, as discussed in this paper, was still mostly informed by the general proclivities of Malaysia artists at that time. Thus, it can be seen that despite the new technology used and explored, the subject matter of these works is still aligned with similar concerns and contents as can be found in contemporaneous works using traditional media. Thus, as this paper demonstrates, the themes of cultural identity and culture related issues and concerns still persisted as the main subject matter of early Malaysian new media artworks, as can be seen in the oeuvres of Hasnul Jamal Saidon, Liew Kungyu, Niranjan Rajah, Yee I-Lann and T.C. Liew.